2010
DOI: 10.1308/003588410x12518836440009
|View full text |Cite
|
Sign up to set email alerts
|

Cervicomastoidfacial versus modified facelift incision for parotid surgery: a patient feedback comparison

Abstract: Ann R Coll Surg Engl 2010; 92: 40-43 40Indications for parotidectomy include benign and malignant tumours as well as inflammatory conditions of the parotid gland.1 Traditionally, the cervicomastoidfacial incision (alternatively known as the modified Blair incision) is used for surgery of the parotid gland which offers excellent surgical access to the parotid gland, but leaves a visible scar in the neck. Alternatively, for suspected benign tumours, a more cosmetic modified facelift (rhytidectomy) incision can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 5 publications
(10 reference statements)
1
37
2
Order By: Relevance
“…Temporary changes to facial movements may happen in between 10% and 70% of cases (Hegazy et al, 2011), andLee et al, (2011) did not observe differences between the incidence of facial paralysis in patients undergoing parotidectomy by the modified facelift incision or the classic Blair approach. Contrary to this, Wasson et al (2010) found a 34% of facial nerve dysfunction in patients operated via the Blair incision, compared to 20% in the cases approached through a modified facelift. In our study, we found a transient facial nerve dysfunction in 15 patients (24%), but in all cases the recovery was spontaneous and complete, irrespectively of the surgical approach.…”
Section: A C C E P T E D Accepted Manuscriptcontrasting
confidence: 62%
“…Temporary changes to facial movements may happen in between 10% and 70% of cases (Hegazy et al, 2011), andLee et al, (2011) did not observe differences between the incidence of facial paralysis in patients undergoing parotidectomy by the modified facelift incision or the classic Blair approach. Contrary to this, Wasson et al (2010) found a 34% of facial nerve dysfunction in patients operated via the Blair incision, compared to 20% in the cases approached through a modified facelift. In our study, we found a transient facial nerve dysfunction in 15 patients (24%), but in all cases the recovery was spontaneous and complete, irrespectively of the surgical approach.…”
Section: A C C E P T E D Accepted Manuscriptcontrasting
confidence: 62%
“…The modified facelift incision is performed to avoid a neck scar and therefore improve cosmetic outcome, but no study has yet measured or compared patient satisfaction of the surgical scar for each approach. Contrary to that published by others in the literatures, intra‐auricular modification of facelift incision group scored better about the postoperative scar compared with the cervicomastoidfacial incision in the follow‐up questionnaire from phone call 7 . Even though we did not experience many cases, our results were encouraging.…”
Section: Discussioncontrasting
confidence: 70%
“…Contrary to that published by others in the literatures, intra-auricular modification of facelift incision group scored better about the postoperative scar compared with the cervicomastoidfacial incision in the follow-up questionnaire from phone call. 7 Even though we did not experience many cases, our results were encouraging. While using intra-auricular modification of facelift incision, the neck and pre-auricular scar which the patients most concerned about could be minimised owing to the following factors: post-auricular hairline incision, retrotragal incision and the abbreviation of extension incision above the tragus.…”
Section: Discussionmentioning
confidence: 68%
“…In pursuit of an alternative cervical incision, Appiani and Delfino [12] described the modified facelift incision (MFI) using a retroauricular incision and positioning the cervical cut posteriorly near the hair line, thus avoiding the most visible part of the scar. It has been argued that the MFI has better cosmetic results than the MBI [13,14]. However, there is still concern that this incision limits surgical exposure.…”
Section: Discussionmentioning
confidence: 99%